Maternal and gestational factors associated with congenital anomalies among live births: a nationwide population-based study in Brazil from 2012 to 2020 - Qeren Hapuk Rodrigues Ferreira Fernandes; Enny S. Paixão; Maria da Conceição Nascimento Costa; Maria Glória Teixeira; Mauricio Lima Barreto; Angelina Xavier Acosta (BMC Pregnancy and Childbirth)
Abstract Background Congenital anomalies are structural and/or functional alterations that contribute significantly to an increase in morbidity and mortality risk observed in children around the world. These disorders are complex, and their occurrence is influenced by a variety of factors, including socioeconomic conditions that play a significant. Understanding these factors is essential to informing targeted preventive strategies for children with congenital anomalies. Thus, this study investigated the socioeconomic and biological factors associated with congenital anomalies in Brazil. Methods We conducted a population-based study using linked data (the birth information system (SINASC) and mortality information system (SIM)), in Brazil from 2012 to 2020. We estimated the odds ratios (ORs) and 95% confidence intervals (CIs) using logistic regression based on a hierarchical model. Initially, a bivariate analysis was carried out to estimate the crude effect of factors associated with congenital anomalies in live births. It was followed by a multilevel framework with three models, in which Model 1 included distal variables, Model 2 added an intermediate variable, and Model 3 incorporated all variables. Results Of the 26,107,682 live births included in this study, 144,291 (0.6%) had congenital abnormalities. Black mothers had higher odds of having children with congenital anomalies (OR 1.16; CI 95% 1.14–1.19) than white mothers, and those without prenatal appointments had an increased chance of having children with congenital anomalies (OR 1.47; CI 95% 1.39–1.56) compared to those who started prenatal care in the first months of pregnancy. Maternal age, more than 40 years (OR 2.26; CI 95% 2.20–2.33), and multifetal gestation (OR 1.49; CI 95% 1.45–1.54) were factors associated with a greater chance of live births with congenital anomalies. Conclusions Our findings indicate that the likelihood of congenital anomalies is highest among live births from the most socially and economically disadvantaged women in Brazil, mainly those who did not have access to adequate prenatal care. In addition, biological characteristics such as advanced maternal age and multifetal pregnancy have also been shown to increase the chances of an affected birth. Understanding the risk factors for the occurrence of births affected by congenital anomalies allows the implementation of actions to reduce exposure to modifiable risk factors, before and during pregnancy.